Manganese zinc ferrite magnetic core with high direct current superposition characteristic and preparation method thereof

By preparing manganese-zinc ferrite cores through specific ratios and processes, the problems of increased loss and performance degradation at high frequencies were solved, achieving low loss, high initial permeability and high DC superposition characteristics, thus improving the stability of the material.

CN121687672APending Publication Date: 2026-03-17SHANDONG KAITONG ELECTRON +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511912373.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing manganese-zinc ferrites exhibit significantly increased losses at high frequencies and a significant decrease in performance with rising temperatures, making it impossible to simultaneously achieve high initial permeability, low loss, and high DC superposition characteristics.

Method used

Using a specific ratio of main and auxiliary components, including Fe2O3, MnO, ZnO, Co2O3, TiO2, CaCO3, SiO2, GeO2, and Y2O3, and through ball milling, pre-calcination, granulation, and sintering processes, the particle size and heating rate are controlled to form a manganese-zinc ferrite core with high DC superposition characteristics.

Benefits of technology

Achieving low loss and high initial permeability at high frequencies improves the DC superposition characteristics of the material and maintains performance stability under different conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a manganese zinc ferrite magnetic core with a high direct current superposition characteristic and a preparation method thereof, and belongs to the technical field of soft magnetic ferrites. The ferrite material comprises a main component and an auxiliary component, wherein the main component is prepared from the following raw materials by mole: 54.5 to 56.5 mol of Fe2O3, 35 to 38 mol of MnO and 6.5 to 8.5 mol of ZnO; and the auxiliary components comprise the following components in percentage by mass: 0.15 to 0.25 wt% of Co2O3, 0.03 to 0.06 wt% of TiO2, 0.02 to 0.04 wt% of CaCO3, 0.008 to 0.015 wt% of SiO2, 0.01 to 0.03 wt% of GeO2 and 0.05 to 0.20 wt% of Y2O3, and the total mass of the main components is 100 wt%. According to the invention, GeO2 and Y2O3 are innovatively introduced and other components are selected for reasonable proportioning and synergistic interaction, so that the direct-current superposition characteristic of the manganese-zinc ferrite is remarkably improved, the low-loss performance under the conditions of 1 MHz and 100 mT is successfully realized, and meanwhile, the manganese-zinc ferrite has high initial permeability and high saturation magnetic flux density under 100 kHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of soft magnetic ferrite technology, specifically relating to a manganese-zinc ferrite core with high DC superposition characteristics and its preparation method. Background Technology

[0002] Currently, soft magnetic ferrites are the most widely used materials. In practical circuits, devices often have a certain DC component during operation, such as choke coils and line output transformers. In this case, ferrite cores not only need good electromagnetic properties but also high DC superposition characteristics, meaning that the attenuation of the core permeability should be as small as possible under superimposed DC conditions. This requires the core material to have high incremental permeability in high DC bias fields. In the field of communications, the core material must maintain relatively stable performance under different operating conditions (such as high f, high B, and high HDC) and environmental conditions (such as temperature changes), which requires the material's permeability value to change linearly with the DC superposition field. It is evident that when using soft magnetic power ferrites at high frequencies, in addition to low power loss, the material must also possess high DC superposition performance. Therefore, developing ferrite materials that enhance current superposition is a necessity for the continuous development of the electronics and information industry.

[0003] The application of manganese-zinc ferrites is limited by the significant increase in loss at high frequencies and the significant decrease in performance with increasing temperature. However, current technologies lack suitable single or combined additives that can achieve initial permeability, reduced high-frequency power loss, and high DC superposition characteristics. Therefore, developing a manganese-zinc ferrite with excellent overall performance and high DC superposition characteristics is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a manganese-zinc ferrite with high DC superposition characteristics, achieving low loss, high initial permeability and high saturation magnetic flux density at high frequencies.

[0005] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials in molar amounts: Fe2O3 54.5-56.5 mol, MnO 35-38 mol, ZnO 6.5-8.5 mol; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, GeO2, and Y2O3.

[0006] Furthermore, the percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.15–0.25 wt%, TiO2 0.03–0.06 wt%, CaCO3 0.02–0.04 wt%, SiO2 0.008–0.015 wt%, GeO2 0.01–0.03 wt%, and Y2O3 0.05–0.20 wt%.

[0007] Furthermore, the purity of the Fe2O3 is greater than 99%.

[0008] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0009] Furthermore, the primary ball milling controls the particle size to ≤1.0μm; the secondary ball milling controls the particle size to less than 0.8μm.

[0010] Furthermore, the heating rate in step (2) is 3°C / min.

[0011] Furthermore, the heating step in step (5) is as follows: heating from room temperature to 600°C at a heating rate of 2°C / min, and heating from 600°C to 1300°C at a heating rate of 5°C / min.

[0012] Furthermore, step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0013] All raw materials used in this invention are commercially available.

[0014] Beneficial effects This invention innovatively incorporates GeO2 and Y2O3 into the manganese-zinc ferrite. 4+ Y 3+As a grain boundary dopant, it can, on the one hand, increase the grain boundary barrier height, suppress carrier migration, reduce eddy current losses, and improve high-frequency resistivity; on the other hand, it refines grain defects, enhances grain boundary bonding strength, suppresses grain boundary migration, prevents abnormal grain growth during sintering, reduces local magnetic domain distortion, and improves permeability consistency under DC bias. Furthermore, Ge 4+ Ion-stabilized lattice defects, optimizing Fe 2+ The distribution significantly improves the incremental permeability under DC superposition.

[0015] This invention adds calcium and silicon elements to the manganese-zinc ferrite. 2+ With Si 4+ During sintering, a Ca-Si-O glassy phase (grain boundary phase) is formed, which inhibits abnormal grain growth, refines grains, increases grain boundary density, and improves resistivity (reducing eddy current loss). Cobalt is also added to this invention. 2+ Fe replacing spinel structure 3+ By introducing positive magnetocrystalline anisotropy to compensate for the negative anisotropy of Mn-Zn ferrite, a magnetocrystalline anisotropy compensation effect is formed, significantly improving DC bias stability. Furthermore, titanium (Ti) is also added to this invention. 4+ Fe replacement 3+ This reduces lattice distortion and high-frequency magnetic loss, while also reducing Ti... 4+ The charge compensation effect inhibits Fe 2+ This process generates and increases resistivity, thereby improving the high-frequency stability of the material and indirectly supporting low-loss characteristics under DC bias.

[0016] This invention innovatively introduces GeO2 and Y2O3, and selects other components in a reasonable ratio to achieve synergistic effects and significantly improve the DC superposition characteristics of manganese-zinc ferrite. It successfully achieves low-loss performance under 1 MHz and 100 mT conditions, while having high initial permeability and high saturation magnetic flux density at 100 kHz. Detailed Implementation

[0017] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.

[0018] Example 1 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 54.5 mol Fe2O3, 35 mol MnO, and 6.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, GeO2, and Y2O3.

[0019] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.15 wt%, TiO2 0.03 wt%, CaCO3 0.02 wt%, SiO2 0.008 wt%, GeO2 0.01 wt%, Y2O3 0.05 wt%.

[0020] The purity of the Fe2O3 is greater than 99%.

[0021] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0022] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0023] The heating rate in step (2) is 3℃ / min.

[0024] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0025] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0026] Example 2 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 55.5 mol Fe2O3, 36 mol MnO, and 7.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, GeO2, and Y2O3.

[0027] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.20 wt%, TiO2 0.04 wt%, CaCO3 0.03 wt%, SiO2 0.012 wt%, GeO2 0.02 wt%, Y2O3 0.07 wt%.

[0028] The purity of the Fe2O3 is greater than 99%.

[0029] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0030] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0031] The heating rate in step (2) is 3℃ / min.

[0032] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0033] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0034] Example 3 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 56.5 mol Fe2O3, 38 mol MnO, and 8.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, GeO2, and Y2O3.

[0035] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.25 wt%, TiO2 0.06 wt%, CaCO3 0.04 wt%, SiO2 0.015 wt%, GeO2 0.03 wt%, Y2O3 0.20 wt%.

[0036] The purity of the Fe2O3 is greater than 99%.

[0037] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0038] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0039] The heating rate in step (2) is 3℃ / min.

[0040] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0041] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0042] Comparative Example 1 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 56.5 mol Fe2O3, 38 mol MnO, and 8.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, and Y2O3.

[0043] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.25 wt%, TiO2 0.06 wt%, CaCO3 0.04 wt%, SiO2 0.015 wt%, Y2O3 0.20 wt%.

[0044] The purity of the Fe2O3 is greater than 99%.

[0045] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0046] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0047] The heating rate in step (2) is 3℃ / min.

[0048] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0049] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0050] Compared with Example 3, this comparative example is identical to Example 3 except that GeO2 is not added to the auxiliary components.

[0051] Comparative Example 2 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 56.5 mol Fe2O3, 38 mol MnO, and 8.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, SiO2, and GeO2.

[0052] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.25 wt%, TiO2 0.06 wt%, CaCO3 0.04 wt%, SiO2 0.015 wt%, GeO2 0.03 wt%.

[0053] The purity of the Fe2O3 is greater than 99%.

[0054] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0055] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0056] The heating rate in step (2) is 3℃ / min.

[0057] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0058] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0059] Compared with Example 3, this comparative example is identical to Example 3 except that Y2O3 is not added to the auxiliary components.

[0060] Comparative Example 3 A manganese-zinc ferrite core with high DC superposition characteristics includes a main component and auxiliary components; the main component is prepared from the following raw materials: 56.5 mol Fe2O3, 38 mol MnO, and 8.5 mol ZnO; the auxiliary components include Co2O3, TiO2, CaCO3, and SiO2.

[0061] The percentages of the auxiliary components to the total mass of the main components are as follows: Co2O3 0.25 wt%, TiO2 0.06 wt%, CaCO3 0.04 wt%, SiO2 0.015 wt%.

[0062] The purity of the Fe2O3 is greater than 99%.

[0063] A method for preparing a manganese-zinc ferrite core with high DC superposition characteristics includes the following steps: (1) One-time ball milling: After loading the main components Fe2O3, MnO and ZnO into the ball mill, add 1.5 times the weight of deionized water and wet ball mill for 4 hours to obtain the main component mixture slurry; (2) Pre-firing: Pre-firing and holding at 950℃ in air atmosphere for 2 hours, then cooling to room temperature to obtain pre-fired material; (3) Secondary ball milling: Add auxiliary components to the above pre-calcined material, load it into a ball mill and stir evenly, then add 1 times the amount of distilled water, ball mill for 8 hours, and dry in an oven at 80℃ for 12 hours; (4) Granulation and pressing: Add 5% by mass of polyvinyl alcohol as the main component to granulate, press to obtain green body; (5) Sintering: The sintering temperature is 1300℃, the sintering temperature is held for 4 hours, and then the temperature is slowly cooled to 1000℃ at a rate of 1℃ / min, and then naturally cooled to obtain manganese zinc ferrite.

[0064] The first ball milling controls the particle size to ≤1.0μm; the second ball milling controls the particle size to less than 0.8μm.

[0065] The heating rate in step (2) is 3℃ / min.

[0066] The heating step in step (5) is as follows: heating from room temperature to 600℃ at a heating rate of 2℃ / min, and heating from 600℃ to 1300℃ at a heating rate of 5℃ / min.

[0067] The step (5) is sintered in an atmosphere with a nitrogen content of 98% and an oxygen content of 2%.

[0068] Compared with Example 3, this comparative example is identical to Example 3 except that GeO2 and Y2O3 are not added to the auxiliary components.

[0069] Performance testing The performance of the samples obtained from the examples and comparative examples was measured.

[0070] The initial permeability μi was measured using an Agilent 4284A LCR precision tester; The saturation magnetic flux density Bs was tested using a BH analyzer. The magnetic loss data of the sample was obtained by using a Keysight 4991B impedance analyzer for spectrum testing. The experiment used the resonant cavity method, and the instrument needed to be calibrated before testing.

[0071] Table 1 Performance Test Results

[0072] As shown in Table 1, the ferrites of Examples 1-3 of this invention, through a reasonable formulation system and a reasonable sintering process, achieved low-loss performance at 1 MHz and 100 mT, and exhibited high initial permeability and high saturation flux density at 100 kHz, giving the manganese-zinc ferrites of this invention high-frequency, high Bs, and high DC superposition characteristics. In contrast, the ferrites of Comparative Examples 1-3, with altered formulations, showed a significant decrease in all their properties, indicating that the GeO2 and Y2O3 components introduced in this invention are indispensable for improving the high DC superposition characteristics of the manganese-zinc ferrites.

[0073] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

Claims

1. A manganese-zinc ferrite core with high DC superposition characteristics, characterized in that, The main component includes the following molar raw materials: Fe2O3 54.5-56.5 mol, MnO 35-38 mol, ZnO 6.5-8.5 mol; the auxiliary component includes Co2O3, TiO2, CaCO3, SiO2, GeO2, Y2O3.

2. The Mn-Zn ferrite core having high DC superposition characteristics according to claim 1, characterized by The percentages of the auxiliary component in the total mass of the main component are: Co2O3 0.15-0.25 wt%, TiO2 0.03-0.06 wt%, CaCO3 0.02-0.04 wt%, SiO2 0.008-0.015 wt%, GeO2 0.01-0.03 wt%, Y2O3 0.05-0.20 wt%.

3. The Mn-Zn ferrite core having high DC superposition characteristics according to claim 1, characterized by The purity of Fe2O3 is greater than 99%.

4. A method of producing a Mn-Zn ferrite core having high DC superposition characteristics as claimed in any one of claims 1 to 3, characterized in that, The preparation includes the following steps: (1) First ball milling: the main components Fe2O3, MnO and ZnO are loaded into a ball mill, 1.5 times weight of deionized water is added, and wet ball milling is performed for 4 h to obtain a main component mixed slurry; (2) Pre-sintering: pre-sintering at 950℃ in air atmosphere for 2 hours, cooling to room temperature to obtain a pre-sintered material; (3) Second ball milling: the auxiliary components are added to the pre-sintered material, stirred uniformly, 1 times of distilled water is added, ball milling for 8 h, and 80℃ oven drying for 12 h; (4) Granulation and compression molding: adding 5% polyvinyl alcohol of the mass fraction of the main component for granulation, compression molding to obtain a green body; (5) Sintering: sintering temperature is 1300℃, sintering for 4 hours, then slow cooling to 1000℃ at a cooling rate of 1℃ / min, and then natural cooling to obtain a manganese-zinc ferrite.

5. The method of producing a Mn-Zn ferrite core having high DC superposition characteristics according to claim 4, characterized by, The particle size of the first ball milling is controlled to be ≤1.0μm; the particle size of the second ball milling is controlled to be less than 0.8μm.

6. The method of producing a Mn-Zn ferrite core having high DC superposition characteristics according to claim 4, characterized by, The heating rate in step (2) is 3℃ / min.

7. The method of producing a Mn-Zn ferrite core having high DC superposition characteristics according to claim 4, characterized by, The heating step in step (5) is: increasing the temperature from room temperature to 600℃ at a rate of 2℃ / min, and increasing the temperature from 600℃ to 1300℃ at a rate of 5℃ / min.

8. The method of producing a Mn-Zn ferrite core having high DC superposition characteristics according to claim 4, characterized by, The sintering in step (5) is carried out in an atmosphere containing 98% nitrogen and 2% oxygen.